Multidrug resistance and its association with Enterobacteriales and age among pregnant Peruvian women with- bacteremia - Antonio M Quispe; Gabriela Soza; Maria J Pons (Journal of Infection in Developing Countries)
Introduction: This study aimed to assess the prevalence of multidrug resistance (MDR) and its associated factors among pregnant Peruvian women with bacteremia.